Thioester‐containing proteins in the tsetse fly (Glossina) and their response to trypanosome infection - Matetovici, I. (Insect Mol Biol, 2018)
Thioester‐containing proteins (TEPs) are conserved proteins with a role in innate immune immunity. In the current study, we characterized the TEP family in the genome of six tsetse fly species (Glossina spp.). Tsetse flies are the biological vectors of several African trypanosomes, which cause sleeping sickness in humans or nagana in livestock. The analysis of the tsetse TEP sequences revealed information about their structure, evolutionary relationships and expression profiles under both normal and trypanosome infection conditions. Phylogenetic analysis of the family showed that tsetse flies harbour a genomic expansion of specific TEPs that are not found in other dipterans. We found a general expression of all TEP genes in the alimentary tract, mouthparts and salivary glands. Glossina morsitans and Glossina palpalis TEP genes display a tissue‐specific expression pattern with some that are markedly up‐regulated when the fly is infected with the trypanosome parasite. A different TEP response was observed to infection with Trypanosoma brucei compared to Trypanosoma congolense, indicating that the tsetse TEP response is trypanosome‐specific. These findings are suggestive for the involvement of the TEP family in tsetse innate immunity, with a possible role in the control of the trypanosome parasite.